2015
DOI: 10.4103/0970-1591.152917
|View full text |Cite
|
Sign up to set email alerts
|

Penile anthropometry in North Indian children

Abstract: Introduction:Physicians frequently encounter questions by parents regarding the normal size of a child's penis. We evaluated normal variations of penile dimensions, correlation of penile length with height, weight, and body mass index (BMI) of boys and analyzed the differences in penile dimensions from those reported from other countries.Materials and Methods:A cross-sectional study was conducted at our institution during October 2012-December 2012. A total of 250 subjects (birth to 10 years) were evaluated an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 12 publications
0
19
3
Order By: Relevance
“…SPL gradually increased from infancy till 9 years of age in our study; similar findings and values have been previously reported by other studies. [512] However, some studies[413141516] have reported slightly higher values. There has been a notable increment in SPL in studies by Park et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SPL gradually increased from infancy till 9 years of age in our study; similar findings and values have been previously reported by other studies. [512] However, some studies[413141516] have reported slightly higher values. There has been a notable increment in SPL in studies by Park et al .…”
Section: Discussionmentioning
confidence: 99%
“…[23] Further, studies that have been conducted previously have suggested that there are variations in penile size in different populations. [45] Thus, the objectives of our study were to present normative data for penile length, testicular volume, and testicular length from birth to 18 years in boys from western Maharashtra and to correlate these parameters with sexual maturity staging (SMR) (with Tanner staging). We also compared data from the present study with available data from Indian and Western studies.…”
Section: Introductionmentioning
confidence: 99%
“…Early recognition of penis size abnormalities is important as it might be the first sign of congenital or endocrine disorders like growth hormone deficiency or hypopituitarism or other disorders of sexual differentiation 1 . Penis length (PL) is reported to vary between different races and ethnici ties [2][3][4][5] . This makes it necessary to establish standard values for penile sizes in healthy neonates in each country.…”
mentioning
confidence: 99%
“…On literature search, we found two studies from India where penile length was measured in children beyond the neonatal age. [57] Both of the studies were from the northern parts of India.…”
Section: Discussionmentioning
confidence: 99%